Interpreting Cemeteries as Part of Tourism Supply: Example of Good Practice - Ostrman Renault, Tanja (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
People have few things in common, and one of them is death that no one can avoid. Fascination with this ultimate deed in someone’s life, philosophies and religions explaining the life after death as well as rituals resulting from their explanations have always been in focus of humans. But can this ultimate act become a tourist attraction? The present paper focuses on a small and unknown cemetery in Alaska as a case study in order to demonstrate that graveyards can offer a variety of opportunities for interpretation. The data was collected on the internet and through the method of observation with participation during the guided visit of Alaska, and the town and cemetery of Skagway.
Keywords: cemetery; dark tourism; death; interpretation of historical facts